High quality nursing based on childlike interest in children with cleft lip and palate: application assessment after operation - Yi Peng; Xiaoyan Hao; Yuan Guo; Xueqin Zhang; Yang Li; Yanmei Ma; Juan Wang (BMC, 2021)
Abstract Purpose The aim of this study was to assess the effect of high-quality nursing based on the concept of childlike interest in children with cleft lip and palate following operation on healing time, degree of pain, psychological state, quality of life, and the occurrence of complications. Methods A series of 62 children with cleft lip and palate was treated in our hospital from January 2019 to March 2021. The patients were randomly divided into observation group (31 cases, given high-quality nursing based on childlike interest) and control group (31 cases, given routine nursing intervention). The healing time and hospital stay of the two groups were recorded. The degree of pain, psychological state and quality of life of the two groups before and after intervention were compared, and the occurrence of complications was closely monitored. Results Compared with the control group, the healing time and hospital stay of the study group were significantly shorter after the intervention (P < 0.05). Before the intervention, no significant difference was identified in pain score between the two groups (P < 0.05), after the intervention, however, the pain score of the study group was significantly lower compared with the control group (P < 0.05). Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) scores of the two groups were comparable before intervention (P > 0.05), while after intervention the SDS and SAS scores of the two groups were lower than those before treatment. Compared with the control group, the SDS and SAS scores of the study group were remarkably lower (P < 0.05). Before the intervention, the quality of life scores of the two groups were comparable (P > 0.05), while after the intervention, the scores of quality of life in the two groups were associated with lower outcomes. Compared with the control group, the scores of quality of life in the study group were significant lower (P < 0.05). After the intervention, there were evident fewer incidence of complications in the study group compared to the control group (P < 0.05). Conclusions High quality nursing based on childlike interest exerted beneficial outcomes in terms of shortening the healing time and hospital stay, reducing the degree of pain and complications, as well as improving the psychological state and quality of life of children harboring cleft lip and palate. Additionally, its high safety feature contributes to the wide application for clinical practice.